Gambaran Pemeriksaan Telur Cacing Soil Transmitted Helminths pada Pekerja Sampah di TPA Suwung dengan Pewarnaan Kunyit Kering dan Eosin Metode Direct Slide - Diani, Ni Luh Ayu Putri Gading; Idayani, Sri; Sudarma, Nyoman (Jurnal Kesehatan Rajawali, 2025)
Soil-Transmitted Helminths (STH) infections are a significant public health issue in tropical regions, particularly among communities with poor sanitation, such as waste workers at the Suwung Landfill in Denpasar. Helminth egg examination is commonly conducted using the direct smear method with eosin staining; however, synthetic dyes have limitations such as high cost and environmental concerns. This study aimed to compare the staining results of STH eggs in fecal preparations using natural dried turmeric dye and eosin through the slide direct method. This research is descriptive in nature, using a qualitative approach. involving 30 STH-positive fecal samples stained using a dried turmeric extract solution (5 g turmeric powder in 20 mL of 96% ethanol) and eosin. Observation parameters included egg color intensity and background contrast. The results showed that staining with dried turmeric revealed 2 positive samples (13.33%), while eosin staining revealed 5 positive samples (33.3%) for STH eggs. The identified helminth species was Ascaris lumbricoides. Eosin was found to be more effective in highlighting the morphology of helminth eggs. However, dried turmeric still shows potential as a supplementary stain due to its accessibility, affordability, and environmental friendliness.